2014
DOI: 10.2174/157016111201140327164641
|View full text |Cite
|
Sign up to set email alerts
|

Association of Platelet Activation with Vascular Cognitive Impairment: Implications in Dementia Development?

Abstract: Cardiovascular risk factors are associated with coronary artery disease (CAD) and with cognitive dysfunction. However, the precise pathogenic mechanisms responsible for this association remain elusive. In the present study, CAD patients with cognitive impairment showed significantly higher platelet activation compared with CAD patients without cognitive impairment. In addition, we identified platelet activity to be a significant independent predictor for the severity of cognitive impairment in these patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Several studies have confirmed that coronary artery disease is associated with cognitive impairment , reduced hippocampal volume and dementia . Recently, Graban and colleagues showed that coronary artery disease was more common in patients diagnosed with vascular dementia compared with controls .…”
Section: Coronary Artery Disease and Myocardial Infarctionmentioning
confidence: 95%
“…Several studies have confirmed that coronary artery disease is associated with cognitive impairment , reduced hippocampal volume and dementia . Recently, Graban and colleagues showed that coronary artery disease was more common in patients diagnosed with vascular dementia compared with controls .…”
Section: Coronary Artery Disease and Myocardial Infarctionmentioning
confidence: 95%
“…Atherosclerosis plays a major role in the development of both coronary artery disease and dementia. In the Cardiovascular Health Study cohort, the incidence of dementia was higher in those with prevalent coronary artery disease,28 and several studies have confirmed that coronary artery disease is associated with cognitive impairment,2931 reduced hippocampal volume,32 dementia due to platelet hyperactivity,33 and increased senile plaque formation in cortical areas of the brain 34. A recent study by Graban and colleagues showed that coronary artery disease was observed more frequently in VaD patients 35.…”
Section: Heart Disease As a Risk Factor For Dementiamentioning
confidence: 95%
“…Approximatively, half of the patients diagnosed with dementia, have additional pathologies associated to the hallmarks of Aβ and tau, including vascular dementia, and dementia with Lewy bodies [ 12 , 13 ]. It is also increasingly recognized that AD and dementia are multifactorial diseases, with contributions to onset and progression including early synaptic failure [ 14 ], inflammation [ 15 ], oxidative stress [ 16 ], mitochondrial dysfunction [ 17 ], cerebrovascular impairment [ 18 , 19 ], depletion of neurotrophins [ 20 , 21 ], and excitotoxicity [ 22 ]. It is argued that effective treatment should target two or more factors in disease pathogenesis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%